Indole Alkaloids from Kopsia hainanensis and Evaluation of Their Antimicrobial Activity - Yang, Yong; Zuo, Wen-Jian; Zhao, You-Xing; Dong, Wen-Hua; Mei, Wen-Li; Dai, Hao-Fu (Planta Medica, 2012)
Three new indole alkaloids, named kopsihainin D (1), kopsihainin E (2), and kopsihainin F (3), along with nine known compounds (4–12) were isolated from the twigs of Kopsia hainanensis. The structures of the new compounds were elucidated by spectroscopic methods including HRESIMS, UV, IR, and NMR. Compounds 1 – 3 and 5 showed inhibitory activity against Staphylococcus aureus with an antibacterial circle diameter of 11.2, 9.1, 10.3 and 9.7 mm, respectively.
Keywords: Kopsia hainanensis; Apocynaceae; indole alkaloids; antimicrobial activity